2016
DOI: 10.1039/c5sm01891a
|View full text |Cite
|
Sign up to set email alerts
|

The selective interactions of cationic tetra-p-guanidinoethylcalix[4]arene with lipid membranes: theoretical and experimental model studies

Abstract: Behavior of cationic tetra-p-guanidinoethylcalix[4]arene (CX1) and its building block, p-guanidinoethylphenol (mCX1) in model monolayer lipid membranes was investigated using all atom molecular dynamics simulations and surface pressure measurements. Members of two classes of lipids were taken into account: zwitterionic 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) and anionic 1,2-dimyristoyl-sn-glycero-3-phospho-l-serine sodium salt (DMPS) as models of eukaryotic and bacterial cell membranes, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The higher biocide effect against Gram positive compared to Gram negative bacteria agrees with the known major susceptibility of Gram positive bacteria versus ammonium quaternary salts. 20 Regarding the mechanism of action, it is plausible that analogously to other polycationic calixarene derivatives, [21][22][23] the antibacterial activity of calix[4]arene derivative 2 is related to the perturbation of the bacterial membrane. Polycationic compound 2 can establish electrostatic interactions with the negatively charged bacterial surface, and hydrogen bonds and hydrophobic interactions involving OH groups and aromatic rings and alkyl chains, respectively, can also occur in the interaction of compound 2 with the bacterial membrane.…”
Section: Antibacterial Activity Of Calix[4]arene Derivative 2 Alone Amentioning
confidence: 99%
“…The higher biocide effect against Gram positive compared to Gram negative bacteria agrees with the known major susceptibility of Gram positive bacteria versus ammonium quaternary salts. 20 Regarding the mechanism of action, it is plausible that analogously to other polycationic calixarene derivatives, [21][22][23] the antibacterial activity of calix[4]arene derivative 2 is related to the perturbation of the bacterial membrane. Polycationic compound 2 can establish electrostatic interactions with the negatively charged bacterial surface, and hydrogen bonds and hydrophobic interactions involving OH groups and aromatic rings and alkyl chains, respectively, can also occur in the interaction of compound 2 with the bacterial membrane.…”
Section: Antibacterial Activity Of Calix[4]arene Derivative 2 Alone Amentioning
confidence: 99%
“…The –O–CO– groups in POPC were practically not involved in hydrogen bond formation (compare both curves in Figure S5 ). It can be noted that the effects observed resemble the flip/flop mechanism described in the case of the CX1 calixarene derivative [ 40 , 43 ].…”
Section: Resultsmentioning
confidence: 78%
“…To obtain a better understanding of the experimental measurements, molecular dynamics simulations were used [ 39 , 40 , 41 , 42 ], which allowed the properties of the model membranes and molecular interaction within the system containing GOTCAB molecules to be studied at an atomic level.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, BaP is highly hydrophobic, thus on first contact with LS, it should accumulate in the monolayer. Our previous studies have shown that such impurities can perturb phase behavior of lipid monolayers . This can in turn lead to LS malfunctioning and respiratory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] On the other hand, BaP is highly hydrophobic, thus on first contact with LS, it should accumulate in the monolayer.O ur previous studies have shown that such impurities can perturb phase behavioro fl ipid monolayers. [33][34][35][36] This can in turn lead to LS malfunctioning and respiratory disorders. In this study we examine the interactions of BaP with LS by means of experimental surface pressure-surface area (P-A)i sotherms and molecular dynamics (MD) simulations at varying surfacea reas.…”
Section: Introductionmentioning
confidence: 99%